2022
DOI: 10.1002/cmdc.202100659
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondria‐Targeted Triphenylphosphonium Conjugated C‐3 Modified Betulin: Synthesis, Antitumor Properties and Mechanism of Action

Abstract: A series of mitochondria-targeted triphenylphosphonium conjugated C-3 modified betulin were synthesized and evaluated against tumor cells. As a result, a new derivative 13 i, the conjugate of 3-O-(3'-acetylphenylacetate)-betulin with triphenylphosphonium, was identified as the one with the best antitumor effect. Conjugate 13 i significantly inhibited HCT116 cells with IC 50 at 0.66 μM. While betulin, C-3 modified betulin, and the triphenylphosphonium moiety showed no inhibition of HCT116 cell proliferation at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…A number of TPP-modified lupane triterpenoids have been synthesized to date, as mono- and bifunctionalized conjugates at the C-2, C-3, C-28, C-29, and C-30 positions (Figure A) with enhanced anticancer activity over the unmodified counterparts. , , ,, …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of TPP-modified lupane triterpenoids have been synthesized to date, as mono- and bifunctionalized conjugates at the C-2, C-3, C-28, C-29, and C-30 positions (Figure A) with enhanced anticancer activity over the unmodified counterparts. , , ,, …”
Section: Resultsmentioning
confidence: 99%
“…A number of TPP-modified lupane triterpenoids have been synthesized to date, as mono-and bifunctionalized conjugates at the C-2, C-3, C-28, C-29, and C-30 positions (Figure 1A) with enhanced anticancer activity over the unmodified counterparts. 43,[47][48][49][50][51][56][57][58][59]88,89 There is a lack of reported syntheses of mixed triterpenoid conjugates, which in addition to the TPP cation would provide additional functional moieties such as carbohydrates. Figure 1B shows the general architecture of the proposed mixed conjugates of BetA, which are modified with the TPP moiety at the C-28 position via an alkylene linker and the monosaccharide moiety at the C-3 position.…”
Section: Synthesis Of Phosphoniohexyl Esters Of 3-o-(glycopyranosyl)b...mentioning
confidence: 99%
“…To date, significant progress has been made in coupling triphenylphosphine groups with small molecule drugs for mitochondria-targeted treatment. [29][30][31] In this study, we successfully synthesized two curcumin derivatives with mitochondrial targeting functions, CUR-T and CUR-2T, which exhibited higher stability than the parent compound CUR. Our in vitro antiproliferative activity study demonstrated that both derivatives had stronger cytotoxicity compared to CUR.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, a mitochondria‐targeted ROS generation inducer may provide a novel strategy to selectively target tumor cells. To date, significant progress has been made in coupling triphenylphosphine groups with small molecule drugs for mitochondria‐targeted treatment [29–31] …”
Section: Discussionmentioning
confidence: 99%
“…After biological assessment, the most promising compound, Bet 29 ( Table 2 ), which was obtained through the conjugation of the previously acetylated betulin derivative (3-O-(3′-acetylphenylacetate)-betulin) with one triphenylphosphonium moiety at the C-28 position, revealed a strong inhibitory effect against HCT116 cancer cells (IC 50 = 0.66 μM) by inducing cycle arrest in the G2/M phase. Furthermore, a structure–activity relationship study on the series of the 19 derivatives suggested that the preferential integration of the triphenylphosphonium moiety into the C28 position might optimize the overall cytotoxic effect [ 42 ].…”
Section: Betulinmentioning
confidence: 99%